Pemberdayaan UMKM Melalui Digital Marketing dan Finance pada UMKM Produk Lokal Kopi Hau - Tini Kartini; Awa, Awa; Didi, Didi; Abdul Hamid; Wati, Feby Anugrah; Nazah, Safinatun; Fattah, Abdul (Universitas 45 Surabaya, 2025)
Business transformation that shifts to digital requires Micro, Small, and Medium Enterprises (MSMEs) to be able to master technology optimally. Many business actors still experience limitations in understanding digital marketing and digital finance, so training is carried out to increase the capacity of MSME actors, one of which is MSMEs of local Kopi Hau products. This service aims to empower MSMEs through the use of digital marketing and digital finance with materials including the use of marketplaces, social marketing strategies, digital financial management, and the creation of marketing content using the CapCut and Canva applications. The results of the activity showed a significant increase in the knowledge and skills of the participants, ranging from online marketing, packaging design, to the use of digital finance such as Warung Books and QRIS. In addition, participants were also guided in managing business legality, including NIB, PIRT, and Halal Labels. This training has been proven to encourage the development of MSMEs, increase competitiveness, expand marketing reach, and strengthen digital literacy. As a result, Hau Coffee MSMEs can develop more adaptively to the demands of the digital era and contribute to local economic growth.